2019
DOI: 10.1136/annrheumdis-2019-216277
|View full text |Cite
|
Sign up to set email alerts
|

Development of a prediction model for inpatient gout flares in people with comorbid gout

Abstract: ObjectivesHospitalisation is a risk factor for flares in people with gout. However, the predictors of inpatient gout flare are not well understood. The aim of this study was to develop a prediction model for inpatient gout flare among people with comorbid gout.MethodsWe used data from a retrospective cohort of hospitalised patients with comorbid gout from Wellington, Aotearoa/New Zealand, in 2017 calendar year. For the development of a prediction model, we took three approaches: (A) a clinical knowledge-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 26 publications
(28 reference statements)
3
26
0
Order By: Relevance
“…Inpatient gout flare is a multifactorial event influenced by a combination of gout-related and hospitalization-related factors. Although no study to date has examined predictors of gout flares exclusively in the critical care setting, several studies have evaluated factors associated with gout flares in the general inpatient setting [10][11][12][13].…”
Section: What Are the Possible Triggers Of Gout Flares In A Critical Care Setting?mentioning
confidence: 99%
See 2 more Smart Citations
“…Inpatient gout flare is a multifactorial event influenced by a combination of gout-related and hospitalization-related factors. Although no study to date has examined predictors of gout flares exclusively in the critical care setting, several studies have evaluated factors associated with gout flares in the general inpatient setting [10][11][12][13].…”
Section: What Are the Possible Triggers Of Gout Flares In A Critical Care Setting?mentioning
confidence: 99%
“…Hypercholesterolemia was also associated with gout flares (odds ratio [95% confidence interval], 2.01 [1.06-3.83]), which might be explained by the correlation of hyperlipidemia with alcohol intake, obesity, and genetic defects [12]. Jatuworapruk et al [13] identified nine predictors of inpatient gout flares in patients with comorbid gout: preadmission serum urate level >0.36 mmol/L, no use of preadmission urate-lowering therapies (ULT), absence of preadmission gout flare prophylaxis, ULT adjustment, initiation, or increased dose of gout flare prophylaxis, tophus, diuretic adjustment, acute kidney injury, and surgery. These predictors were likely to be associated with gout flares by causing sudden changes in serum urate levels or due to the suboptimal control of gout, all of which increased the risk of gout flares.…”
Section: What Are the Possible Triggers Of Gout Flares In A Critical Care Setting?mentioning
confidence: 99%
See 1 more Smart Citation
“…Inpatient gout flare is a multifactorial event influenced by a combination of gout-related (e.g., serum urate level, tophus) and hospitalization-related factors (e.g., diuretic adjustment, acute kidney injury, surgery) [2]. Surgery may be associated with gout flare through more than one mechanisms, including volume status change, tissue hypoxia and systemic inflammatory response [3,4].…”
Section: Kanon Jatuworaprukmentioning
confidence: 99%
“…Inpatient gout flare is associated with worse hospital outcomes. Previous studies suggested that inpatient gout flare contributed to an additional five to six days of hospital admission, 5,6 higher healthcare costs 7 and higher chance of adverse events related to gout flare medications 8 …”
Section: Introductionmentioning
confidence: 99%